Sodium Hyaluronate Nanocomposite Respirable Microparticles to Tackle Antibiotic Resistance with Potential Application in Treatment of Mycobacterial Pulmonary Infections - Irene Rossi; Francesca Buttini; Fabio Sonvico; Filippo Affaticati; Francesco Martinelli; Giannamaria Annunziato; Diana Machado; Miguel Viveiros; Marco Pieroni; Ruggero Bettini (MDPI AG, 2019)
Tuberculosis resistant cases have been estimated to grow every year. Besides Mycobacterium tuberculosis, other mycobacterial species are responsible for an increasing number of difficult-to-treat infections. To increase efficacy of pulmonary treatment of mycobacterial infections an inhalable antibiotic powder targeting infected alveolar macrophages (AMs) and including an efflux pump inhibitor was developed. Low molecular weight sodium hyaluronate sub-micron particles were efficiently loaded with rifampicin, isoniazid and verapamil, and transformed in highly respirable microparticles (mean volume diameter: 1 μm) by spray drying. These particles were able to regenerate their original size upon contact with aqueous environment with mechanical stirring or sonication. The in vitro drugs release profile from the powder was characterized by a slow release rate, favorable to maintain a high drug level inside AMs. In vitro antimicrobial activity and ex vivo macrophage infection assays employing susceptible and drug resistant strains were carried out. No significant differences were observed when the powder, which did not compromise the AMs viability after a five-day exposure, was compared to the same formulation without verapamil. However, both preparations achieved more than 80% reduction in bacterial viability irrespective of the drug resistance profile. This approach can be considered appropriate to treat mycobacterial respiratory infections, regardless the level of drug resistance.